Lean Manufacturing practices and operational performance improvements: a case study in an amazon company - Araújo, Marcos Araújo de (2025)
This article aims to analyze the operational performance of the main product family of a textile industry company, under the prism of Lean Manufacturing practices, proposing improvements in the Finishing macroprocess. The methology applied was a case study, with an exploratory nature. This proposition was made based on the elaboration of two different productive scenarios, classified as future state map 1 and future state map 2. Comparing them with the current state map, the future state map 1 made it possible to readjust the productive capacity, reduce excess production and lead time in the order of 88,6%, in addition to increasing efficiency by 59%. In turn, future state map 2 made it possible to obtain better control/reduction of intermediate stocks, providing a reduction in lead time by 70,5%. Therefore, this study is considered relevant to the company under study, given the analyzes and proposals generated.